The successful study within the framework of the proceedings of exemption from the obligation to pay child support for adult children - Tucto Santamaría, César Jean Frank (2022)
It is common for judges to find ourselves in situations where there are regulatory gaps, understanding these as situations not carefully contemplated in our legal system. In fact, the topic we present deals with an aspect to which the Civil Code does not provide a proper conceptualization, and, therefore, forces judges to make a biased interpretation —many times— of what the legislator wanted to imply. In this sense, in this normative analysis there are different interpretations that we give to the ‘successful study’ within the judiciary, which means that justice is not predictable in a uniform way at the national level. Thus, this study seeks to shed light on interpretation for the judiciary, a background for future research, and legal culture for lawyers, law students, and the public.